2009
DOI: 10.1016/j.febslet.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dual activity of certain HIT‐proteins: A. thaliana Hint4 and C. elegans DcpS act on adenosine 5′‐phosphosulfate as hydrolases (forming AMP) and as phosphorylases (forming ADP)

Abstract: Edited by Hans Eklund Keywords:Histidine triad-family protein Dual catalytic activity Adenosine 5 0 -phosphosulfate hydrolysis Adenosine 5 0 -phosphosulfate phosphorolysis a b s t r a c t Histidine triad (HIT)-family proteins interact with different mono-and dinucleotides and catalyze their hydrolysis. During a study of the substrate specificity of seven HIT-family proteins, we have shown that each can act as a sulfohydrolase, catalyzing the liberation of AMP from adenosine 5 0 -phosphosulfate (APS or SO 4 -pA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…The supposition that NH 2 -pA occurs in other organisms and that its concentration can be enzymatically controlled is supported by the existence of adenosine-, or generally nucleoside-5′-phosphoramidate hydrolases (EC 3.9.1.-) that catalyze cleavage of the substrate P-N bond and liberate the corresponding 5′-NMP (pN) and ammonia from NH 2 -pA or other NH 2 -pNs. This catabolic activity has been demonstrated in D. discoideum (Rossomando & Hadjimichael, 1986), rat liver (Kuba et al, 1994), and appears to be a catalytic feature of various HIT-proteins (Bieganowski et al, 2002;Guranowski et al, 2008;2010a;2010b). Our preliminary studies showed that NH 2 -pA can be hydrolyzed by at least two enzymes from yellow lupin -dinucleoside triphosphatase/Fhit homolog protein (EC 3.6.1.29) and nucleoside phosphoramidase (Hint protein) (Guranowski et al, 2006).…”
Section: Introductionsupporting
confidence: 59%
“…The supposition that NH 2 -pA occurs in other organisms and that its concentration can be enzymatically controlled is supported by the existence of adenosine-, or generally nucleoside-5′-phosphoramidate hydrolases (EC 3.9.1.-) that catalyze cleavage of the substrate P-N bond and liberate the corresponding 5′-NMP (pN) and ammonia from NH 2 -pA or other NH 2 -pNs. This catabolic activity has been demonstrated in D. discoideum (Rossomando & Hadjimichael, 1986), rat liver (Kuba et al, 1994), and appears to be a catalytic feature of various HIT-proteins (Bieganowski et al, 2002;Guranowski et al, 2008;2010a;2010b). Our preliminary studies showed that NH 2 -pA can be hydrolyzed by at least two enzymes from yellow lupin -dinucleoside triphosphatase/Fhit homolog protein (EC 3.6.1.29) and nucleoside phosphoramidase (Hint protein) (Guranowski et al, 2006).…”
Section: Introductionsupporting
confidence: 59%
“…In addition to C10F3.4 and C15orf58, a mycobacterial protein (Rv2613c) containing a HXHXH motif has also recently been reported to act as a phosphorylase (on diadenosine tetraphosphate) and not as a hydrolase (27). Furthermore, A. thaliana Hint4 and C. elegans DcpS, two HIT proteins containing the HXHXH motif, have been shown to display a phosphorolytic activity toward adenosine 5Ј-phosphosulfate in addition to their hydrolytic activity on this substrate (28). The phosphorylase activity of the latter two enzymes, however, was minor compared with their hydrolase activity at neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of these proteins in peroxisomes appears to be a plant-specific phenomenon, as the Arabidopsis HIT PTSs are also conserved in their homologs in other plant species such as rice (Table 1). A recent in vitro study showed that most of the Arabidopsis HIT proteins can function as sulfohydrolases by catalyzing the conversion of adenosine 5′-phosphosulfate (APS) to AMP and sulfate (SO42; Guranowski et al, 2010). This study also showed that, in the presence of orthophosphate (P i ), HIT1/Hint4 exhibited APS phosphorylase activity as well, resulting in the formation of ADP.…”
Section: Some Novel Aspects Of Plant Peroxisomes Revealed By Experimementioning
confidence: 99%